Genomic studies in Montana Tropical Composite cattle - Grigoletto, Laís (2020)
Beef cattle production is a major component of the Brazilian economy and places the country amongst the top worldwide beef producers and exporters. The development and use of composite populations represent a promising alternative to increase production efficiency and quality in beef cattle. The strategic combination of different breeds poses a great opportunity to maximize genetic variability and exploit heterosis and breed complementarity. In order to successfully implement genomic evaluations for beef cattle, various genomic approaches and methodologies need to be investigated. In addition, the majority of genomic models and methods currently used for genomic evaluations were developed based on purebred animals and the knowledge on the use of genomic information in synthetic or composite cattle breeds is still very limited. Therefore, studies investigating more sophisticated methodologies and genomic approaches will enable a more efficient use of the genomic information available for composite breeds and consequently, more accurate breeding values. The overall objectives of this thesis are to: 1) identify genomic regions and potential candidate genes associated with various economically important traits in composite beef cattle populations; 2) investigate genomic selection methodologies and imputation strategies to improve the accuracy of genomic prediction of breeding values in the genetically diverse population of Montana Tropical Composite® cattle. Approximately 4,000 genotyped animals from multiple breeds (Montana, Nellore, Aberdeen Angus, Red Angus, Senepol, and Simmental) and SNP chip panels were available for this research. In summary, this project contributed to the application of genomic approaches to fastener genetic progress for a variety of economically important traits in composite beef cattle and increase the profitability of beef producers.